Resolution-Constrained Quantization With JND-Based Perceptual-Distortion Measures - Moo Young Kim; Kleijn, W.B. (IEEE signal processing letters, 2006)
When the squared error of observable signal parameters is below the just noticeable difference (JND), it is not registered by human perception. We modify commonly used distortion criteria to account for this phenomenon and study the implications for quantizer design and performance. Taking the JND into account in the design of the quantizer generally leads to improved performance in terms of mean distortion and the number of outliers. Moreover, the resulting quantizer exhibits better robustness against source mismatch